O PERCURSO SENSACIONISTA NA POÉTICA DE ÁLVARO DE CAMPOS: TRÊS MOMENTOS - Locatelli, Cristina Alves (Revista Desassossego, 2009)
This paper shows how the journey of sensacionismo is made in Alvaro de Campos’s poetry. Starting with more theoretical assumptions as the concept of vanguard and the futuristic / symbolist influence in that movement, then analyzes of the poems are made in order to score how the sensacionismo is effective not only as aesthetic theory of Portuguese poetry at the beginning of the twentieth century, but and also artistic and poetically over the work of the poet in question.